(untitled) (Research, Society and Development, 2022)
Dental record has a fundamental role in dentist performance. This study evaluated the standard registration of dental records of patients submitted to endodontic treatment for undergraduate students (CG) and specialists endodontics students (CE) in a public university in the south of Brazil. The sample was obtained by convenience, consecutively and included dental records patients of a public university in the south of Brazil who were treated at CE and clinical records of patients who were treated at CG, during on the year 2014. Was analyzed the description of endodontic treatment, data retrieved was scored and rated using a modification of the scoring system proposed by Streiner & Norman (1996) and quality of radiographs was performed according to the guidelines of “National Radiological Protection Board”. At dental records were analyzed, 223 belong to CG and 219 belong CE. The records from CE and CG had similar information on the evaluated parameters, except for “presence of rubber dam” and “presence of abbreviature in the description” (Mann-Whitney Test, P = 0.386). The absence of periapical radiographs was higher in CE than CG records (CE = 36.77%; CG = 0.46%). (Mann-Whitney test, P<0.0001). There was a predominance of periapical radiographs with the grades “excellent” and “diagnostically acceptable” in both groups.The quality of records generally obtained good results. The incorporation of new science into the educational program like electronic records and digital imaging techniques, facilitating the constant updating of data related to health and treatment of patients improving the record of the evolution of procedures.